2020
DOI: 10.1080/09638288.2020.1717651
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion through folk high school in Sweden – the experience of young adult students with high-functioning autism

Abstract: Purpose: The purpose of this study is to provide a description of the learning environment at Folk High School for participants with high-functioning autism and to examine their learning experience at Folk High School. Methods: A qualitative interview study was conducted with 21 participants who were enrolled at Folk High School which had been adapted to suit young adults with high-functioning autism. The interviews were analysed by means of a thematic content analysis which resulted in the identification of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
(57 reference statements)
0
10
0
2
Order By: Relevance
“…This approach can be linked to the FHS's institutional values and principles and the social and meaningful dimensions which stem from the holistic view that knowledge is related to a person's whole life situation (Andersén, 2011;Bjursell & Nordvall, 2016;Paldanius, 2007). As previous research (Hugo & Hedegaard, 2020) has also noted, the fact that teaching at FHSs is centred on the participant also means that participants are provided with the opportunity to work at their own pace and they are not stressed by demands of achieving certain goals within a set time limit, as is the case in other schools. The result of this is that it often takes somewhat longer to complete various courses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This approach can be linked to the FHS's institutional values and principles and the social and meaningful dimensions which stem from the holistic view that knowledge is related to a person's whole life situation (Andersén, 2011;Bjursell & Nordvall, 2016;Paldanius, 2007). As previous research (Hugo & Hedegaard, 2020) has also noted, the fact that teaching at FHSs is centred on the participant also means that participants are provided with the opportunity to work at their own pace and they are not stressed by demands of achieving certain goals within a set time limit, as is the case in other schools. The result of this is that it often takes somewhat longer to complete various courses.…”
Section: Discussionmentioning
confidence: 96%
“…Social learning is of particular relevance to people with HFA because they often suffer from a lack of social competence (Barnhill, 2007;Fiske & Taylor, 2013;Gillberg & Ehlers, 2006;Happé & Frith, 2006;Striano & Reid, 2008); note that this lack of social competence is a potential obstacle to obtaining gainful employment (Attwood, 2008) and becoming more socially included. Previous studies , 2020 have demonstrated the importance of social learning, especially since it provides opportunities for people with HFA to develop the ability to create social relationships and social networks, to have the courage to ask for help, and to engage in public speaking. Social learning can also be associated with formal learning and, as such, constitutes its own subject content.…”
Section: Education As Rehabilitation and Habilitationmentioning
confidence: 99%
“…Lärares förmåga att se och erkänna visar sig vara en viktig didaktisk strategi för att nå kursdeltagarnas förutsättningar och behov. Att pedagogiken baseras på kursdeltagarnas behov och förmågor och dess betydelse för kursdeltagarna påvisas i några studier som fokuserar på kursdeltagare med funktionsvariationer och deras lärmiljö (Bernhard & Andersson, 2017;Hugo & Hedegaard, 2021;Nylander m.fl., 2015). I dessa studier framträder lärarnas arbete indirekt genom kursdeltagarnas berättelser i form av enkäter och intervjuer samt statistiska data.…”
Section: Lärares Arbete I Folkhögskolans Pedagogiska Praktikunclassified
“…2018;Folkbildningsrådet, 2015;SCB, 2020). Lärarnas engagemang beskrivs samtidigt bidra till att kursdeltagarna upplever sig sedda, bekräftade och förstådda vilket även bekräftas av lärarna själva som uttrycker en strävan efter att bemöta kursdeltagare utifrån deras behov och anpassa undervisningen efter dessa (Fejes m.fl., 2018;Hugo m.fl., 2019;Hugo & Hedegaard, 2021;Nylander m.fl., 2015).…”
Section: Lärares Arbete I Folkhögskolans Pedagogiska Praktikunclassified
“…27 Before the school year 2011/2012, which cover most of the study period, students needed to obtain at least a passing grade in three subjects (English, mathematics, and Swedish, including Swedish as a second language) to be considered eli- pace than regular high school, and adaptability toward specific student needs. 29,30 Folk high schools commonly offer the same programs as regular high schools, while often providing vocational or aesthetic programs as well. Both folk high school and municipal adult education also allow students to retake failed classes from their basic compulsory education.…”
Section: Description Of Setting and Variablesmentioning
confidence: 99%